Comparative transcriptome profiling provides insights into the growth promotion activity of Pseudomonas fluorescens strain SLU99 in tomato and potato plants - Hanifah, Nurul Atilia Shafienaz binti; Ghadamgahi, Farideh; Ghosh, Samrat; Ortiz, Rodomiro; Whisson, Stephen C.; Vetukuri, Ramesh R.; Kalyandurg, Pruthvi B. (Frontiers in Plant Science, 2023)
The use of biocontrol agents with plant growth-promoting activity has emerged as an approach to support sustainable agriculture. During our field evaluation of potato plants treated with biocontrol rhizobacteria, four bacteria were associated with increased plant height. Using two important solanaceous crop plants, tomato and potato, we carried out a comparative analysis of the growth-promoting activity of the four bacterial strains: Pseudomonas fluorescens SLU99, Serratia plymuthica S412, S. rubidaea AV10, and S. rubidaea EV23. Greenhouse and in vitro experiments showed that P. fluorescens SLU99 promoted plant height, biomass accumulation, and yield of potato and tomato plants, while EV23 promoted growth in potato but not in tomato plants. SLU99 induced the expression of plant hormone-related genes in potato and tomato, especially those involved in maintaining homeostasis of auxin, cytokinin, gibberellic acid and ethylene. Our results reveal potential mechanisms underlying the growth promotion and biocontrol effects of these rhizobacteria and suggest which strains may be best deployed for sustainably improving crop yield.